Morphological Engineering of Battery-Type Cobalt Oxide Electrodes for High-Performance Supercapacitors - Boddu Haritha; Mudda Deepak; Obili M. Hussain; Christian M. Julien (Physchem)
Nanomaterials have attracted significant attention in recent decades for their diverse applications, including energy storage devices like supercapacitors. Among these, cobalt oxide (Co3O4) nanostructures stand out due to their high theoretical capacitance, unique electrical properties, and tunable morphology. This study explores the hydrothermal synthesis of Co3O4, revealing that the molar ratio of cobalt nitrate to potassium hydroxide significantly influences the morphology, crystal structure, and electrochemical performance. An optimized 1:1 molar ratio (COK 11) yielded well-defined cubic nanostructures with uniform elemental distribution, as confirmed by SEM, TEM, and EDS analyses. Structural characterization through XRD, XPS, and FTIR validated the formation of the Co3O4 spinel phase with distinctive lattice and surface oxygen features. Electrochemical property analysis demonstrated the superior performance of the COK 11 electrode, achieving a high specific capacity of 825 ± 3 F/g at a current density of 1 A/g, a rate capability of 56.88%, and excellent cycle stability of 88% at 3 A/g after 10,000 cycles. These properties are attributed to the nano-cubic morphology and interconnected porosity, which enhanced ion transport and active surface area. This study highlights the importance of synthesis parameters in tailoring nanomaterials for energy storage, establishing COK 11 as a promising candidate for next-generation high-performance supercapacitor applications.